2003
DOI: 10.1159/000074679
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging as a Diagnostic Tool in Dementia with Lewy Bodies

Abstract: Due to similar presenting symptoms, many physicians find it difficult to distinguish cases of dementia with Lewy bodies (DLB) from Alzheimer’s disease or Parkinson’s disease with dementia. The pathologic diagnosis of DLB has improved because of the discovery of probes for α-synuclein, a protein found in Lewy bodies. However, pathologic diagnosis can be employed postmortem only, and therefore diagnostic techniques that can be employed to guide patient management are still needed. Consensus criteria have been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Mori et al [10] showed that the visuoperceptual disability in DLB patients plays a role in the development of visual hallucinations by a neuropsychological study. With several neuroradiological studies, DLB patients were found to exhibit a more prominent hypoactivity in the occipital lobe than AD patients, which may be responsible for visual hallucinations in DLB patients [4][5][6][7][8] . In this study, the DLB group exhibited significantly lower perfusion in the occipital and other regions than the AD group with 3DSRT, as shown in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mori et al [10] showed that the visuoperceptual disability in DLB patients plays a role in the development of visual hallucinations by a neuropsychological study. With several neuroradiological studies, DLB patients were found to exhibit a more prominent hypoactivity in the occipital lobe than AD patients, which may be responsible for visual hallucinations in DLB patients [4][5][6][7][8] . In this study, the DLB group exhibited significantly lower perfusion in the occipital and other regions than the AD group with 3DSRT, as shown in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroradiological or neuropathological studies examining such a pathomechanism in DLB patients have detected hypoactivity in the occipital lobe [4][5][6][7][8] or Lewy pathology in the secondary visual pathway [9] . On the other hand, such a pathomechanism may also be detected by neuropsychological tests examining visuoperceptual and/or constructional disabilities [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…These studies revealed that DLB is characterized by low glucose metabolism and decreased regional cerebral blood flow in the occipital cortex, which distinguishes it from AD. [8][9][10] On the other hand, structural changes in DLB were found to closely resemble those in AD. Volumetric studies have consistently shown a loss of GM in the MTLs, including the hippocampus and amygdala, in patients with DLB.…”
mentioning
confidence: 94%
“…In DLB, a deficit in CMRglc has been observed in the temporal, parietal, occipital, and cerebral cortices (44,45). The hallucinations that are a clinical symptom of DLB are likely a correlate of a reduction of CMRglc in the primary visual cortex (46); in contrast, metabolic activity in the primary visual cortex is usually well preserved in AD.…”
Section: Brain Glucose Metabolismmentioning
confidence: 99%